2019
DOI: 10.1063/1.5091359
|View full text |Cite
|
Sign up to set email alerts
|

Study of Y-type hexaferrite Ba0.5Sr1.5ZnNiFe12O22 powders

Abstract: We report results from a study on the influence of the substitution of Zn 2+ cations in the Y-type Ba0.5Sr1.5Zn2Fe12O22 hexaferrite, known for strong magnetoelectric coupling, with magnetic cations, such as Ni 2+ , on its structural and magnetic properties. Polycrystalline samples of Ba0.5Sr1.5ZnNiFe12O22 were synthesized by citric acid solgel auto-combustion. The saturation magnetization value of 54.7 emu/g at 4.2 K was reduced to 37.2 emu/g at 300 K. The temperature dependence of the magnetization at magneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(21 citation statements)
references
References 12 publications
2
18
1
Order By: Relevance
“…Another maximum at 40 K is also seen -it arises from the magnetic phase transformation from a spiral magnetic order to a conical spin order at low temperatures. Such a maximum was not observed in our earlier study on the Ba0.5Sr1.5ZnNiFe12O22 powder [9]; this indicates that replacing the Zn 2+ ionic species with the smaller Mg 2+ cations [19] leads to important changes in the paths of magnetic interactions leading to a conical spin structure arising at low temperatures. The ZFC and FC curves showing a stable magnetisation growth at temperatures approaching 300 K means that the temperature of transformation to a paramagnetic state exceeds this temperature, so that this transition could not be registered in the experiments reported here.…”
Section: Resultscontrasting
confidence: 66%
See 2 more Smart Citations
“…Another maximum at 40 K is also seen -it arises from the magnetic phase transformation from a spiral magnetic order to a conical spin order at low temperatures. Such a maximum was not observed in our earlier study on the Ba0.5Sr1.5ZnNiFe12O22 powder [9]; this indicates that replacing the Zn 2+ ionic species with the smaller Mg 2+ cations [19] leads to important changes in the paths of magnetic interactions leading to a conical spin structure arising at low temperatures. The ZFC and FC curves showing a stable magnetisation growth at temperatures approaching 300 K means that the temperature of transformation to a paramagnetic state exceeds this temperature, so that this transition could not be registered in the experiments reported here.…”
Section: Resultscontrasting
confidence: 66%
“…The synthesis of Y-type hexaferrites is commonly accompanied by the formation of different oxides, usually spinels, mainly because the temperature range for synthesising the Y-phase is rather narrow. However, in what concerns the magnetic phase transitions, our previous studies [9,12,13] on other Y-hexaferrite compositions have shown that the trace amount of spinel ferrites in the material studied does not affect the magnetic-phase transition temperatures. In figure 2, we display the initial magnetisation and the hysteresis curves of the Ba0.5Sr1.5NiMgFe12O22 powder at 300 K and 4.2 K. As seen, the magnetisation curves for both temperatures do not reach saturation at the highest magnetic field used of 50 kOe, the highest magnetisation values being 32 emu/g and 24 emu/g respectively at 4.2 K and 300 K. The magnetisation values determined are typical for Y-type hexaferrites.…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…The average thickness of the Ba 2 Mg 2 Fe 12 O 22 particles was 380 nm. A similar microstructure was observed for Ba 0.5 Sr 1.5 Zn 2 Fe 12 O 22 . , …”
Section: Synthesis Techniques Of Y-type Hexaferritessupporting
confidence: 79%
“…The precursors produced by these co-precipitation methods are synthesized at 1170 °C. We described in detail such a procedure for the synthesis of different Y-type hexaferrites. We also reported , a comparative investigation on this synthesis method’s effect on the microstructural and magnetic parameters of Ba 2 Mg 2 Fe 12 O 22 powder materials and found that the ultrasonically assisted co-precipitation produced particles with a practically perfect hexagonal shape compared with the particles obtained by sol–gel autocombustion (Figure b). The average thickness of the Ba 2 Mg 2 Fe 12 O 22 particles was 380 nm.…”
Section: Synthesis Techniques Of Y-type Hexaferritesmentioning
confidence: 99%